2017
DOI: 10.1016/j.fluid.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of trimer self-assembly under shear

Abstract: The self-assembly of patchy trimer particles consisting of one attractive site and two repulsive sites is investigated with nonequilibrium molecular dynamics simulations in the presence of a velocity gradient, as would be produced by the application of a shear stress on the system. As shear is increased, globular-shaped micellar clusters increase in size and become more elongated. The globular clusters are also more stable at higher temperatures in the presence of shear than at equilibrium. These results help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Depending on its intensity, shear may be used to exfoliate 2D materials like LDH 14 and graphene 15 or induce structuring 16 . The effects of shear on non-classical mechanisms of growth such as self-assembly have yet to be fully elucidated, though recent simulations have shown that the OA of patchy trimer particles is accelerated under certain shear rates 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on its intensity, shear may be used to exfoliate 2D materials like LDH 14 and graphene 15 or induce structuring 16 . The effects of shear on non-classical mechanisms of growth such as self-assembly have yet to be fully elucidated, though recent simulations have shown that the OA of patchy trimer particles is accelerated under certain shear rates 17 .…”
Section: Introductionmentioning
confidence: 99%
“…clusters could form, but at sufficiently higher shear rate, the patchy attraction can not sustain shear force and the cluster breaks up. A similar increase in mean cluster size with shear rate was found in a system of patchy trimers, which contain an attractive site and two repulsive sites at a distance L from the attractive site with bond angles of 60 • [141]. Selfassemblies of hydrogel patchy particles were shown to bear large curvature variance with the increase of shear rates due to the high flexibility and the ability of adjusting orientation spontaneously [96].…”
Section: Self-assembly In External Fieldmentioning
confidence: 69%
“…The crystals assembled by Agg I appeared in the bulk aqueous solution, while Agg II completely covered the surface of the droplets, presenting a hydrogel shell (Figure f). This rapid assembly of Agg II is due to the fact that, when the dispersed droplets remained in a state of constant motion, the transient shear generated between the droplets’ surface and the bulk solution would promote a rapid arrangement of hydrophobic sides at the interface, thereby accelerating the interface-induced assembly kinetics. To corroborate shear accelerated assembly, hexadecane was further rapidly added to the CEP supersaturated solution to produce transient interfacial shear, and the rapid emergence of interface-induced hydrogels was clearly observed (Movie S1). A similar conclusion was obtained by reversing the solution addition, with the CEP supersaturated solution being added to hexadecane (Movie S2).…”
Section: Results and Discussionmentioning
confidence: 92%